Extraction model of low methoxyl pectin from apple pomace effects of acid concentration and time on the process and the product - Fertonani, Heloísa Cristina Ramos; Scabio, Ardalla; Carneiro, Eliana Beleski Borba; Schemin, Maria Helene Canteri; Nogueira, Alessandro; Wosiacki, Gilvan (My University, 2009)
In Brazil, one of the top apple producing countries in the world, apple processing is an increasing activity, with pomace as the main by-product. To extract pectin from pomace, factors affecting process and product should be studied for optimization. A model to produce LMP directly from dried apple pomace was established observing the effects of HNO3 concentration and the time of reaction at 97oC, analyzed from a statistical and practical point of view. The model for gravimetric yield (R2 =0.9834) predicts the highest value of 20.07 g/100 g (126 mM; 14.07 min) of a pectin with a degree of esterification of 48.49%. The model for degree of esterification of extracted pectin (R2= 0.9797) predicts the lowest value of 43.73% (200 mM; 10.07 min) with a yield of 16.77g/100 g. The results using the central coordinates (100 mM; 10 min) for gravimetric yield were 19.01 g/100 g and for the degree of esterification, 50.79%.
Keywords: Apple; Pectin; Extraction; LMP; Nitric acid